Wear and corrosion properties of laser cladded Cu47Ti34Zr11Ni8/SiC amorphous composite coatings on AZ91D magnesium alloy - 黄开金 闫里 王存山 谢长生 周昌荣 (Transactions of Nonferrous Metals Society of China, 2010)
To improve the wear and corrosion properties of AZ91D magnesium alloys, Cu-based amorphous composite coatings were fabricated on AZ91D magnesium alloy by laser cladding using mixed powders of Cu47Ti34Zr11Ni8 and SiC. The wear and corrosion behaviours of the coatings were investigated. The wear resistance of the coatings was evaluated under dry sliding wear condition at room temperature. The corrosion resistance of the coatings was tested in 3.5% （mass fraction） NaCl solution. The coatings exhibit excellent wear resistance due to the recombined action of amorphous phase and different intermetallic compounds. The main wear mechanisms of the coatings and the AZ91D sample are different. The former is abrasive wear and the latter is adhesive wear. The coatings compared with AZ91D magnesium alloy also exhibit good corrosion resistance because of the presence of the amorphous phase in the coatings.